Analisis Laporan Keuangan Berbasis SAK EMKM dalam Meningkatkan Efektivitas dan Efisiensi Pengelolaan Keuangan pada Toko Emas H. Pakistan Daulay - Syaikhah Putri Alifiah Siregar; Rahmi Syahriza; Hendra Harmain (SAFE-Network, 2026)
This study aims to analyze the application of Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) in improving the effectiveness and efficiency of financial management at the H. Pakistan Daulay Gold Shop in Padang Lawas Regency. This study used a descriptive qualitative approach with a case study method. Data were obtained through in-depth interviews, direct observation, and documentation studies. Data were then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that before the implementation of SAK EMKM, the shop's financial practices were still traditional, with manual recording, mixing of personal and business funds, and intuitive decision-making. After the implementation of SAK EMKM in 2022, significant changes occurred in the financial reporting system, allowing the owner to prepare three main reports the Statement of Financial Position, the Income Statement, and the Notes to the Financial Statements (CaLK) in a systematic and measurable manner. The implementation of SAK EMKM has been proven to improve the accuracy of financial information, strengthen transparency and accountability, and support data-driven decision making. Furthermore, this standard also contributes to administrative efficiency, cash flow control, and improved managerial capabilities of business owners. This research confirms that the implementation of SAK EMKM is not only a reporting instrument but also a strategic tool in building effective, efficient, and sustainable financial governance for MSMEs. These findings are expected to serve as a reference for the government, academics, and business actors in strengthening accounting literacy and encouraging the professionalization of financial management in the MSME sector in Indonesia.